Eksport EWG do Polski w latach 1968-1980. Uwarunkowania koniunkturalne - Brzeziński, Marian; Kowalski, Tadeusz (Wydział Prawa i Administracji UAM, 1983)
The article presents a model describing fluctuations related to changes in the exporter's economic activity (EEC). Model assumptions were adapted to specificities of the East-West trade. The study related to the EEC exports to Poland was to answer the following questions: what is the effect of the EEC business tendencies on a growth of the EEC-Poland export volume, does a cyclical character of that export yields any negative impact on a developement of current production and growth dynamics in Poland. The effect of internal factors on the economic system of Poland resulting in a phenomenon of a cyclical development was neglected here. The relationships discussed in this study were treated as a factor fostering or weakening internal fluctuations. A statistical survey conducted in the years of 1968 -1980 proved that there is a possibility of forming peculiar economic mechanisms in the EEC-Poland trade which can cause importing negative cycles of business activity of the EEC by the Polish economy. The study indicated only at a one possible aspect of the EEC-Poland trade examining phenomena related to imports from the EEC and leaving the problems of exports from Poland aside. It would be fallacious to search the main reasons for the cyclical developement of Polish economy in the relationships presented in this study. Nevertheless, the research conducted indicates that exports from the EEC must be treated as a non-controlled variable or not entirely controlled one on account on a lack of grounds to rule out its cyclical character.
The EEC exports to Poland in 1968 -1980. Business cycle contingencies